Insurers and Insured Individuals Interaction as Basis for Persistent Agricultural Production Process; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 26 : Responsible Research and Innovation (RRI 2016) - Moiseev A. Alexandr (2017, 2017)
Title screen